A Distorted Circadian Clock Causes Early Flowering and Temperature-Dependent Variation in Spike Development in the Eps-3Am Mutant of Einkorn Wheat. Issue 4 (1st April 2014) - Gawroński, Piotr; Ariyadasa, Ruvini; Himmelbach, Axel; Poursarebani, Naser; Kilian, Benjamin; Stein, Nils; Steuernagel, Burkhard; Hensel, Goetz; Kumlehn, Jochen; Sehgal, Sunish Kumar; Gill, Bikram S; Gould, Peter; et al.
Abstract: Viable circadian clocks help organisms to synchronize their development with daily and seasonal changes, thereby providing both evolutionary fitness and advantage from an agricultural perspective. A high-resolution mapping approach combined with mutant analysis revealed a cereal ortholog of Arabidopsis thaliana LUX ARRHYTHMO / PHYTOCLOCK 1 ( LUX / PCL1 ) as a promising candidate for the earliness per se 3 ( Eps-3A m ) locus in einkorn wheat ( Triticum monococcum L.). Using delayed fluorescence measurements it was shown that Eps-3A m containing einkorn wheat accession KT3-5 had a distorted circadian clock. The hypothesis was subsequently confirmed by performing a time course study on central and output circadian clock genes, which showed arrhythmic transcript patterns in KT3-5 under constant ambient conditions, i.e., constant light and temperature. It was also demonstrated that variation in spikelet number between wild-type and mutants is sensitive to temperature, becoming negligible at 25°. These observations lead us to propose that the distorted clock is causative for both early flowering and variation in spike size and spikelet number, and that having a dysfunctional LUX could have neutral, or even positive, effects in warmer climates. To test the latter hypothesis we ascertained sequence variation of LUX in a range of wheat germplasm. We observed a higher variation in the LUX sequence among accessions coming from the warmer climate and a unique in-frame mutation in early-flowering Chinese T. turgidum cultivar 'Tsing Hua no. 559.' Our results emphasize the importance of the circadian clock in temperate cereals as a promising target for adaptation to new environments.